Analisis Strategi Diferensiasi Produk Dalam Upaya Meningkatkan Volume Penjualan Pada Usaha Mikro Kecil Dan Menengah (UMKM) Berdasarkan Perspektif Bisnis Syariah (Studi Pada Produk Buak Tat Kehago Lampung) - Fatih Fuadi; Annastasya Ayu Saputri (Jurnal Ekonomi dan Bisnis Digital, 2023)
The development of regional specialty food businesses is increasingly mushroominghis business is a business with great prospects, seen from the number of tourists who are starting to look at Lampung as a tourist destination. Because there are so many similar businesses, this results in competition, especially in terms of products. To overcome this, entrepreneurs must determine a product differentiation strategy that can increase sales. This research uses field research, a qualitative approach, primary and secondary data sources and uses observation and interview methods obtained from informants related to the research problem. This research uses the research object of Buak Tat Kehago Lampung products. The results of the research can be concluded that the product differentiation strategy in increasing sales implemented by Kehago Lampung is quite good and effective. After the data was collected and analyzed, the researcher succeeded in obtaining the following findings: the product differentiation strategy variables used by Kehago Lampung are mutually sustainable and related to each other. Which of the shapes, features, quality of performance, quality of suitability, durability, reliability, easy to repair, style and design are the focus of the strategy used by Kehago Lampung as an effort to increase sales. The product differentiation strategy implemented has had a positive impact, namely an increase in sales of Buak Tat products. This can be seen from the sales graph which has increased from the previous year, and is also supported by a sales system that keeps up with the times (offline and online).